2012
DOI: 10.1074/jbc.m112.384545
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Activates Hepatic 5′-AMP-activated Protein Kinase through Sympathetic Nervous System and α1-Adrenergic Receptor

Abstract: Background: AMPK activation promotes glucose and lipid metabolism. Results: Hepatic AMPK activities were decreased in fatty liver from lipodystrophic mice, and leptin activated the hepatic AMPK via the ␣-adrenergic effect. Conclusion: Leptin improved the fatty liver possibly by activating hepatic AMPK through the central and sympathetic nervous systems. Significance: Hepatic AMPK plays significant roles in the pathophysiology of lipodystrophy and metabolic action of leptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…Novel peptides mimicking the a2 AMPK domain increase the AMPK phosphorylation in the skeletal muscle but not in the liver, which leads to reduced adipose tissue mass and triglyceride levels in the skeletal muscle and increased liver triglyceride levels (44). Furthermore, AMPK activity in skeletal muscle and liver is differentially regulated in lipodystrophic A-ZIP/F-1 mice, in which AMPK activity in the skeletal muscle of A-ZIP/F-1 mice is unchanged, while AMPK activity in liver is reduced (45). In contrast to our results, hemin reduces lipid accumulation in the liver of Zucker rats and db/db mice, which is accompanied with reduced expression of inflammatory cytokine (15,46).…”
Section: Discussionmentioning
confidence: 99%
“…Novel peptides mimicking the a2 AMPK domain increase the AMPK phosphorylation in the skeletal muscle but not in the liver, which leads to reduced adipose tissue mass and triglyceride levels in the skeletal muscle and increased liver triglyceride levels (44). Furthermore, AMPK activity in skeletal muscle and liver is differentially regulated in lipodystrophic A-ZIP/F-1 mice, in which AMPK activity in the skeletal muscle of A-ZIP/F-1 mice is unchanged, while AMPK activity in liver is reduced (45). In contrast to our results, hemin reduces lipid accumulation in the liver of Zucker rats and db/db mice, which is accompanied with reduced expression of inflammatory cytokine (15,46).…”
Section: Discussionmentioning
confidence: 99%
“…Because leptin affects 5-AMP-activated protein kinase and FA oxidation in the liver by stimulating the hepatic α 1 -AR, negative feedback regulation of ADRA1 mRNA might occur by the leptin status in the liver of neonatal calves. Therefore, adrenergic effects on hepatic FA oxidation might be mediated by α 1 -and β 2 -AR as well as plasma leptin concentrations (Lafontan and Berlan, 1993;Miyamoto et al, 2012).…”
mentioning
confidence: 99%
“…However, whether these reductions in hepatic and muscle steatosis are secondary to decreased caloric intake and weight loss, or due to a direct effect on fatty acid oxidation in non-adipose tissue, cannot be determined from these studies. Based on recent experimental data in lipodystrophic mice, which showed that increase in 5´-AMP activated protein kinase activity in liver and skeletal muscle after leptin treatment [43], it is likely that leptin exerts its effects by both central and peripheral mechanisms, the relative importance of each needs to be determined by future controlled experiments.…”
Section: Mechanisms Of Leptin Actionmentioning
confidence: 99%